Dracula [videorecording (DVD)] - Langella, Frank; Olivier, Laurence, 1907-1989; Pleasence, Donald; Nelligan, Kate, 1951-; Stoker, Bram, 1847-1912 (2004)
Throughout history Dracula has filled the hearts of men with terror and the hearts of women with desire. This stylish new production of the classic gothic horror tale stars Frank Langella, repeating his electrifying, award-winning stage performance as the blood-thirsty Count, and Laurence Olivier as the devout vampire hunter Von Helsing who is Dracula's nemesis. A great cast, fine direction, and a superbly atmospheric musical score make this the ultimate Dracula.